Wall-motion tracking in fetal echocardiography-Influence of frame rate on longitudinal strain analysis assessed by two-dimensional speckle tracking. - Enzensberger, Christian; Achterberg, Friederike; Graupner, Oliver; Wolter, Aline; Herrmann, Johannes; Axt‐Fliedner, Roland (Echocardiography, 2017)
Background Frame rates (FR) used for strain analysis assessed by speckle tracking in fetal echocardiography show a considerable variation. The aim of this study was to investigate the influence of the FR on strain analysis in 2D speckle tracking. Methods Fetal echocardiography was performed prospectively on a Toshiba Aplio 500 system and a Toshiba Artida system, respectively. Based on an apical or basal four-chamber view of the fetal heart, cine loops were stored with a FR of 30 fps (Aplio 500) and 60 fps (Artida/Aplio 500). For both groups (30fps and 60fps), global and segmental longitudinal peak systolic strain (LPSS) values of both, left (LV) and right ventricle (RV), were assessed by 2D wall-motion tracking. Results A total of 101 fetuses, distributed to three study groups, were included. The mean gestational age was 25.2±5.0 weeks. Mean global LPSS values for RV in the 30 fps group and in the 60 fps group were −16.07% and −16.47%, respectively. Mean global LPSS values for LV in the 30 fps group and in the 60 fps group were −17.54% and −17.06%, respectively. Comparing global and segmental LPSS values of both, the RV and LV, did not show any statistically significant differences within the two groups. Conclusion Performance of myocardial 2D strain analysis by wall-motion tracking was feasible with 30 and 60 fps. Obtained global and segmental LPSS values of both ventricles were relatively independent from acquisition rate.